Inter Simple Sequence Repeat (ISSR) Analysis of Neolamarckia cadamba in Sarawak - Pang Shek, Ling; Ho Wei, Seng (2011)
Sarawak state government’s aspiration to establish one million hectares of planted forests by the year 2020 has only achieved 25 % thus far. It is estimated that at least 30 million of seedlings are needed for annual planting and reforestation. One of the problems causing the slow rate in the establishment of planted forest, despite of the huge number of seedlings needed, is the availability of quality planting materials. To overcome this problem, a tree improvement programme focusing on Neolamarckia cadamba or locally known as Kelampayan was initiated in July 2007. The Kelampayan tree improvement programme is a long-term investment to increase the productivity of forest plantations by providing a source of improved planting stock that will improve the tree growth, better form and wood quality as well as pest and disease resistance. To date, two Kelampayan provenance trials have been established since 2008 in Landeh and Niah, Sarawak. This study is directed at the understanding of the genetic diversity and relatedness of the Kelampayan planted in Block 4 at the Landeh provenance trial using inter simple sequence repeat (ISSR) markers. A total of 34 ISSR markers commonly used in plant genotyping were screened using Kelampayan DNA. Out of these markers, 11 were found to be polymorphic and reproducible. PCR optimizations were carried out on these selected 11 ISSR markers. Genotyping of the Kelampayan using the selected ISSR markers is performed at optimal temperatures (Ta) varying from 44 to 61C. The optimum conditions for these ISSR are as follow: 2ng of DNA template, 2mM MgCl2, 0.5 U Taq DNA polymerase, 0.2mM dNTPs and 10 M primer. The genetic information obtained from this study will be used as one of the parameters for the selection of genetically diverse and nonrelated plus trees from the Landeh provenance trial for future tree improvement programme.